2012
DOI: 10.1007/s00240-012-0463-5
|View full text |Cite|
|
Sign up to set email alerts
|

The comparison of laparoscopic pyelolithotomy and percutaneous nephrolithotomy in the treatment of solitary large renal pelvic stones

Abstract: The aim of the study is to investigate whether laparoscopic pyelolithotomy (LPL) could find a place in the management of large renal pelvic stones which are generally considered as excellent indications for percutaneous nephrolithotomy (PNL). Between 2006 and 2009, 26 consecutive patients with large (>4 cm(2)) renal pelvic stones were treated by LPL and their charts were compared to 26 match-paired patients treated with PNL during the same period. The patients were matched for age, BMI, stone size and location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…Recently, some studies have reported favorable results using LP, with stonefree rates of 88.9%-100% in managing solitary renal pelvic stones. [9][10][11][12] In our study, the stone-free rate in Group I (located only in the pelvis) was 96.7% (29/30), which is comparable to results reported by other centers. LP, therefore, should be considered a feasible modality in the management of renal pelvic stones.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, some studies have reported favorable results using LP, with stonefree rates of 88.9%-100% in managing solitary renal pelvic stones. [9][10][11][12] In our study, the stone-free rate in Group I (located only in the pelvis) was 96.7% (29/30), which is comparable to results reported by other centers. LP, therefore, should be considered a feasible modality in the management of renal pelvic stones.…”
Section: Discussionsupporting
confidence: 89%
“…8 Recently, some previous studies published high success rates using LP for patients with solitary renal stones. [9][10][11][12] However, the effects of stone burden and location on the surgical outcomes of LP have yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…21,24,25 When compared with PNL, one outstanding advantage of LPL is that it is harmless to the parenchyma. 26 Therefore, the risk of bleeding is higher in PNL related to the access localization and dilation technique. Bleeding is the most important and frequent complication in PNL.…”
Section: Discussionmentioning
confidence: 99%
“…They defined this as a new indication for laparoscopy in a developing country. Tefekli and colleagues 26 reported their experience with LPL in 26 patients with solitary pelvic stone in comparison with matched group of PNL; their stone free rate was 100% and 88.4%, respectively.…”
Section: Associated Anomaliesmentioning
confidence: 99%
“…Ülkemizde yapılan LP ile PNL'yi karşılaştıran bir çalış-mada, PNL grubunda operasyon süresi ve hastanede kalış süresinin daha kısa, LP grubunda ise kan kaybının daha az olduğu, taşsızlık oranlarının ise benzer olduğu gösterilmiştir (19). LP'nin soliter böbrekte PNL ile karşılaştırılmasında, taşsızlık oranları, kan kaybı, hastanede kalış süreleri ve morbidite açısından benzer olduğu ancak operasyon süresinin LP'de daha uzun olduğu gösterilmiştir (20).…”
Section: Böbrek Taşlarıunclassified